Teacher Candidates’ Learning Strategies and Academic Self-Efficacy Levels: Is There a Relation Between the Two? - Akçaoğlu, Mustafa Öztürk (Cumhuriyet International Journal of Education, 2016)
The current study aimed to identify teacher candidates’ learning strategies and academic self-efficacy levels. Furthermore, the correlations between these variables and gender and departments were looked into. The study was mainly descriptive and correlational. The sample of the study consisted of 256 teacher candidates enrolled at a faculty of education. To collect data, The Motivated Strategies for Learning Questionnaire (MSLQ) and Academic Self-Efficacy Scale were used. During the analysis phase of the study besides descriptive statistics, bivariate correlation and multivariate analysis of variance were carried out. The findings revealed that there was a significant correlation between the learning strategies rehearsal, organization, metacognitive self-regulation, association, time/study environmental, and peer learning and help seeking. The results MANOVA revealed significant relations between rehearsal, organization, metacognitive self-regulation strategies and departments and gender. Furthermore, the findings indicated that the teacher candidates had an overall high academic self-efficacy levels.
Keywords: Learning strategies; academic self-efficacy; gender; teacher candidates; Öğrenme stratejileri; akademik öz-yeterlik; cinsiyet; öğretmen adayı; 2. Zero hunger; 4. Education; 8. Economic growth